Comparación de la prevalencia y severidad de caries y su relación con estilo de vida en instituciones educativas de la comuna 11 y 13 de Ibagué 2019 (2020)
It is important to know what is the prevalence and severity of caries in children between 2 and 5 years of age, to contribute with the necessary elements in planning educational interventions that favor the development of oral health. Prevention is the most important factor in modern dentistry, since knowledge of risk factors, methods of promotion and oral prevention must be applied in dental patients, in order to improve oral health status. Objective. To compare the prevalence, severity of caries and its relationship with lifestyle in educational institutions in Ibagué 2019. Method. Descriptive, cross-sectional observational study; with a convenience sample of 68 children aged 2 to 5 years based on the informed consent of the Child Development Centers Los Pitufos Américas and Los Pitufos Colinas del Sur, from communities 11 and 13 respectively. The survey was used as information gathering techniques, with a script of 23 specific questions, which aimed to evaluate practices and beliefs related to oral habits, nutrition, lifestyle and ICDAS, as well as the University's ethics committee. Antonio Nariño, Ibagué Headquarters, issued the concept of project viability, since it is classified in the minimum risk category, according to resolution 8430 (1993). Result. A prevalence of dental caries of 80% was found in the children of the CDI southern hills, while in the children of the CDI the Americas was 90%. According to the severity criteria of the ICDAS code, it was determined that the CO of the American headquarters was 06 in teeth 85 with 44% and in southern hills 05 in teeth 74 with 59%. Likewise, among the factors that were found most prevalent in children with dental caries are the habits of digital sucking, taking a bottle, and correspondence with families whose parents have incomplete secondary education, socioeconomic income less than or equal to a minimum wage, and those who were affiliated with the subsidized health system, although without significant differences Conclusions. In this study it was found that clinical, sociodemographic, and behavioral variables were associated with the severity of caries lesions. These clinical variables were the presence of structural defects in the enamel and the presence of dentobacterial plaque; between sociodemographic, the child's age and socioeconomic level; and in the behavioral ones, the frequency of tooth brushing, lifestyles (oral hygiene, feeding) variables that are related to the prevalence of caries (ceod> 0).